Wplus multifunctional cutting box (One'z Holding) / Wan Aliff Hafizul Wan Shaharuddin Shah ... [et al.] - Wan Aliff Hafizul, Wan Shaharuddin Shah; Nor Hafizah, Zulkapli; Sir Mohamad Adam Arif, Mohamad; Anis Aqilah, Abd Razak; Nur Shafiqah, Sapiee (2020)
The main objective of creating this report is for us to learn on how to manage a company from every single aspect from start to the finish. We have to decide on who is going to be a CEO of the company and who is going to be the marketing, administrative, operational and financing manager. All the task had been divided based on our department and we have to make sure that all the plan that we do will meet with the company’s objective. For the introduction of this eportm it is focus on to introduce of this company which is call One’z Holding and also the nature of this company, where it is located, when is the company first commence and many more. The next on is to get to know the company’s logo, motto vision and mission. There is also the background of each one of the manager in different department including the CEO background. Normally it consists of the full name, phone number, their picture and most importantly is their job scope so that people will know who is working in each of department. Other than that, there is also an explanation of the product that the company produce and sell which is call WPlus Multifuction Chopping Box. The next one is the marketing plan focus on how to attract more customer to purchase our product, consist on marketing objective, the market size, market trend, market segmentation, and many more. There is also an explanation of the forecast sales that our company target. Last but not least there is also a marketing budgeting that is really important for the financial manager. For the operational plan which focus on producing our product, there is a process planning for manufacturing, production planning, type of material, machine, and equipment that are needed to make our product. There is also a manpower planning overhead requirement, license, and operational budget. For administrative plan, it consist of the organizational chart, list of administrative personnel, task and responsibility, remuneration, all of the furniture and fittings needs and also administrative budget. Finally for financial plan, it is focus on the money, the company budget and so forth, consist of project implementation cost and source of finance, manage the fixed asset, load, the performance of cash flow, income statement, balance sheet, and financial ratio analysis which help the company to see their performance through time. 13 In conclusion, this business plan helped us on how to manage a company, how to create and idea for a product and how to sell it so that the company can earn more profit.